A tunable triode-MOSFET transconductor and its application to g(m)-C filters - De Lima, J. A.; Dualibe, C. (Institute of Electrical and Electronics Engineers (IEEE), 1999)
A linear, tunable CMOS transconductance stage is introduced. Drain voltage of the input transistor operating in triode region is settled by a regulation loop and a first-order linear relationship between g(m) and a de bias voltage is achieved. In addition to easy tuning, this technique offers circuit simplicity, wide dynamic range, high input and output impedances and low consumption. The transconductor is presented on both single-ended and fully-differential versions. A 3rd-order elliptical low-pass g(m)-C filter with a nominal roll-off frequency of 2MHz is used as one example for the many applications of the proposed transconductor. SPICE data describe circuits performances and filter tunabilily Passband is tuned at a rate of 2.36KHz/mV and good linearity is indicated by a 0.89% THD for an 800mV(p-p) balanced-driven input.